A Case Study : Development of Modified Physical Education Learning Equipment to Increase Students’ Learning Enthusiasm and Interest in Sports - Herry Setiawan; Enno Malik Ibrahim (Journal of Physical Education Health and Sport, 2026)
Physical Education, Sports, and Health (PE) instruction in elementary schools continues to encounter several challenges, including inadequate infrastructure, limited variation in instructional strategies, and low levels of student engagement in physical activities. These constraints highlight the necessity for innovative approaches to learning, one of which involves the development of modified instructional equipment tailored to the characteristics and needs of students.This study aims to analyze the role of modified PE learning equipment in enhancing students’ enthusiasm for learning and their interest in sports activities at the elementary school level. The research adopts a Systematic Literature Review (SLR) approach by critically examining a range of prior studies relevant to the development of learning media and equipment modification in physical education. The review process involves systematic stages of identification, selection, and analysis of scholarly articles focusing on innovations in instructional media, sports-based learning activities, and equipment modification.The findings indicate that the implementation of modified PE learning equipment significantly contributes to increased student participation, improved motor skill development, heightened learning motivation, and greater interest in sports. Learning media designed with innovative and game-based approaches are proven to foster a more engaging, interactive, and enjoyable learning environment, thereby encouraging students to participate more actively in physical education activities.In conclusion, the development of modified PE learning equipment represents a viable and effective alternative for improving the quality of physical education instruction in elementary schools, while simultaneously promoting a more active and positive attitude toward sports among students.